(untitled) (Research, Society and Development, 2025)
Introduction: Performance evaluation has emerged as a strategic management tool, contributing to professional development, the qualification of care, and the alignment of institutional goals. Objective: to reveal the performance evaluation process carried out by nurses in relation to nursing workers undergoing functional readaptation at a university hospital in the southern region of Brazil. Methodology: a qualitative and descriptive study carried out at a university hospital in the southern region of Brazil. Nineteen nurses linked to the Single Legal Regime participated, working in different services or support units, through semi-structured interviews. The data were analyzed and interpreted according to content analysis, Minayo’s operational proposal. Results: the information converged into two categories, namely: communication, as one of the strategies used by nurses; and evaluation as a management tool. Conclusion: the nurses used communication as the main element in the evaluation process and in the daily observation process of the worker, without using formal methods.